Marital Satisfaction of Second Wives Undergoing Siri Polygamy among Orêng Kênêk - M. Sholihin; Koentjoro (Indigenous: Jurnal Ilmiah Psikologi, 2023)
Abstract.Polygamy is not only practiced by kiai, officials, klebun, or blater (fighters) but also practiced by orêng kênêk, such as farmers, fishermen, drivers, pedicab drivers and people who do not have permanent jobs and other. This study aims to determine the marital satisfaction of second wives undergoing siri polygamy in orêng kênêk in Bnagkalan Madura Regency. Marital satisfaction is described by each individual's subjective assessment of the overall quality of the marriage. Data collection used interview techniques with semi-structured interview guidelines. There were 3 participants selected in this research using the purposive sampling technique, with the following criteria: 1) Madurese women among orêng kênêk with a final education of junior high school; 2) undergoing polygamy as a siri second wife; 3) the marriage age is more than five years; 4) aged between 40-60 years. This study uses a phenomenological qualitative approach with an Interpretative Phenomenological Analysis (IPA). The results of the research show that the marital satisfaction of second wives undergoing siri polygamy among orêng kênêk is described in two master themes, including: 1) positive acceptance of polygamy, which contains the meaning of polygamy as God's destiny, awareness of being a second wife as well as an attitude of submission and patience as an adaptation process; and 2) Satisfaction with polygamy which includes achieving perfection in life, positive relationship with husband, commitment to marriage and gratitude. The findings can be applied to increase marital satisfaction for second wives in facing siri polygamy.